Stenting for acute cerebral venous sinus thrombosis in the superior sagittal sinus - Adachi, Hidemitsu (Interv Neuroradiol, 2015)
Endovascular treatment for superior sagittal sinus (SSS) thrombosis is not always successful because of difficult access and long thrombus lesions. We report the first two cases of patients with acute cerebral venous sinus thrombosis at the SSS that was not recanalized by anticoagulation, mechanical thrombectomy, or thrombolysis, but was successfully treated by stent placement. Case 1 was a 37-year-old woman with bilateral subdural hematomas. Digital subtraction angiography showed obstruction of the sinus from the SSS to the right transverse sinus. Recanalization was achieved by selective thrombolysis using urokinase followed by balloon angioplasty, but re-occlusion occurred on the next day of treatment. Repeated endovascular treatment including balloon angioplasty, thrombus aspiration and thrombolysis using recombinant tissue plasminogen activator failed to achieve recanalization. We thus placed intracranial stents in the SSS, which did achieve recanalization. Case 2 was a 69-year-old woman with a small infarction in the left parietal lobe. Digital subtraction angiography showed sinus obliteration from the SSS to the bilateral transverse sinuses. Recanalization was not achieved by balloon angioplasty, thrombus aspiration and selective thrombolysis. We thus placed intracranial stents in the SSS, which did achieve recanalization. Postoperative course was uneventful in both cases and venous sinus patency was confirmed by venography >1.5 years after treatment. When conventional endovascular strategies have been unsuccessful, placement of intracranial stents, which can easily gain access to the distal part of the SSS as compared with carotid stents, may be a useful treatment option for the acute sinus thrombosis in this region.